The ecology model and influencing factors in Adana province (Annals of Medical Research, 2021)
Aim: The relationship between the individuals and their health care attitudes is known as ‘The Ecology of Medical Care’. The present study aims at revealing the ecology of medical care in our province. Material and Methods: A questionnaire form was applied to 685 individuals from 396 houses between May 1st, 2009 and June 15th, 2009.Results: Mean age of 685 subjects was 36.6±13.8 years (18-83). Of them, 504 (73.57%) were females, 520(75.91%) were married; 212 (42.06%) of the females and 61 (33.70%) of the males were graduates of elementary school; 479 (69.92%) were migrated to Adana from another region; 577 (84.23%) had social insurance. When the participants had a health problem, 262 (38.24%) preferred primary care. Of the subjects, 540 (78.83%) reported a health problem and 296 (39.30%) admitted to the physician, received 333 diagnoses during the recent 30 days. Of 333 diagnoses, 133 (39.93%) were made at primary care. 264 (38.54%) subjectshad a chronic disease and 192 (49.70%) preferred secondary care for follow up.Conclusion: While individuals prefer primary care worldwide when they have a health problem, this was found to be secondary care in our study. Comprehensive and patient-centered services may increase the sense of trust and interest toward primary care.
Keywords: Ecology model; patient centeredness; primary care